The Heroism Value in Totokng Dance at The Nurutni’ Ceremony Dayak Salako Community in West Kalimantan - Slamet, Deni; Tati Narawati; Agus Budiman (Mudra : jurnal seni budaya, 2025)
This study aims to explore and analyse the heroism values embodied in the Totokng dance, a traditional ritual performed as part of the Nurutni’ ceremony by the Dayak Salako community in West Kalimantan. These values play a crucial role in shaping collective character and preserving cultural identity amid the pressures of globalisation and the ongoing crisis in character Education. The research is driven by the limited academic attention given to the dimension of heroism within the cultural expressions of the Dayak people, particularly in the context of rice harvest rituals. Adopting a qualitative method with an ethnographic approach, the study collected data through participant observation, semi-structured interviews, documentation, and literature review. Informants were purposively selected based on their direct involvement in the tradition. The findings reveal that the Totokng dance conveys heroism values such as courage, sacrifice, solidarity, responsibility, and loyalty. These values are expressed through symbolic movements, the social roles of the dancers, and the spatial design of the performance, all of which are rooted in spiritual and historical relationships. Rather than functioning solely as an aesthetic performance, the dance serves as a medium for transmitting values and as a tool for character Education grounded in local wisdom. These findings reaffirm the importance of preserving intangible cultural heritage as a key component of sustainable development and multicultural Education in Indonesia.